O filme “Bicicletas de Nhanderu” revelando processos de hibridação cultural - Fuzaro, Karina (2015)
This dissertation was dedicated to the study of indigenous culture, specifically the Guarani Mbya, who live in São Miguel das missões - Rio Grande do Sul. We sought to reflect on what the Indians tell of their culture, what elements are present in the everyday life that resemble Western culture and which challenges are being addressed. faced by the Indians due to the intense contact with the "whites". To answer these questions, we have selected a film from this community entitled Bicycles of Nhanderu, produced by the Video Project in Villages, where the main filmmakers are the members of the community themselves. From the visual and sonorous description of each scene, using the technique of decupage, we sought to reflect on the symbols, rituals and actions of the daily life of both the relationship of man with nature, and the relationship between himself and himself , mainly to allow the film to reveal the processes of cultural hybridization, in an attempt to demystify the images present in various media discourses, which place the Indians with subjects intact, immutable, isolated and with an ecologically correct way of life. The theoretical perspective that guided all the work is inscribed in the field of cultural studies, with emphasis on Stuart Hall and Nestor Canclini, since these authors consider the identity of the subjects in permanent reconstruction, and feel the cultural hybridization as a natural and necessary process for the survival of the indigenous culture. In summary, based on the analyzed images and discussions, it is possible to be said that we learn in a significant way how the indigenous culture really is. In addition, we realize that the community being studied is allowing itself to be challenged at all times, because living as "good savages" is no longer the best way to survive in such an immediacy and capitalist world.